Kritik Sosial pada Kumpulan Cerpen Aud Kelor Karya Carma Citrawati Analisis Sosiologi Sastra - Ayu Sulastri, Ni Kadek; Sutama, Putu (Humanis; Vol 25 No 3 (2021)DO - 10.24843/JH.2021.v25.i03.p12, 2021)
This research entitled “Social Criticism in Aud Kelor Short Story Collection by Carma Citrawati Analysis of Literary Sociology”. There are three short stories that were studied, namely the short stories entitled Wayan Kelor, Siaappp Presiden, and Keneh Pasih . The three short stories were analyzed by structural theory from Nurgiyantoro and sosiology of literature from Wellek and Warren. This research aims to describe the narative structure, the author’s background, and social criticism contained in the three short stories. Methods and techniques used in this study was divided into three stages. The stages of methods and data collection techniques used two methods, namely the simak and record technique. The stages of methods and data analysis techniques using qualitative methods supported by analytic descriptive techniques. Methods and techniques for presenting the results of data analysis using informal methods are supported by inductive techniques and deductive techniques. The result from this research is structure narative from the three short stories, namely: incidents, plot, characters and characterizations, settings, themes, and moral value of the stories. The second research result is an explanation of the author's biography. The third research result is social criticism contained in the three short stories, namely: injustice in law, education, politic, and socio-cultural. The author conveys the social criticism through characters and themes. This social criticism is conveyed specifically to readers and in general to society and the government. The author aims to make readers aware to open their mindset to their surroundings.